Assessing Impact of Liberalization on Financial Performance Sustainability of Indian Pharmaceutical Industry using Structure Conduct Performance Model - et.al, Dr. Pankaj Talreja (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Indian Pharmaceutical Industry is ranked third largest by volume and fourteenth by value. It thus accounts for 10% of world’s production by volume and 1.5% by value according to Department of Pharmaceuticals, Government of India. Recognizing the immense potential for growth of Indian pharmaceutical industry and its direct impact on Indian economy the present paper tries to analyze the market structure of the Indian pharmaceutical firms and assess how the sustainable profitability of firms is affected using structure conduct performance model. The study founds out the sustainable profitability is statistically related to firm size, export and import, raw material expenses, power use and wage intensity but there seems to be insignificant effect of market share and mergers and acquisition on firm’s performance in terms of sustainable profitability.